Single‐Cell and Spatial Transcriptomics Decodes Wharton's Jelly‐Derived Mesenchymal Stem Cells Heterogeneity and a Subpopulation with Wound Repair Signatures (Adv. Sci. 4/2023). Issue 4 (3rd February 2023) - Chen, Penghong; Tang, Shijie; Li, Ming; Wang, Dezhi; Chen, Caixiang; Qiu, Yiqun; Fang, Zhuoqun; Zhang, Haoruo; Gao, Hangqi; Weng, Haiyan; Hu, Kailun; Lin, Jian; et al.
Abstract : Wharton's Jelly‐Derived Mesenchymal Stem Cells In article number 2204786, Jinghua Chen, Liangwan Chen, Xiaosong Chen, and co‐workers chart a comprehensive spatiotemporal heterogeneity atlas of Wharton's jelly‐derived mesenchymal stem cells (WJ‐MSCs), finding that S100A9 + CD29 + CD142 + WJ‐MSCs exhibit promising wound‐repair properties which is uncannily parallel to the cover story, Chinese myth of Nüwa mending the heaven. Nüwa (single‐cell omics) rushed out of riprap (mixed WJ‐MSCs) with the crystal stone (S100A9 + CD29 + CD142 + WJ‐MSCs), and repaired the holes (skin wound) precisely. This study envisions important insights on cell subpopulations to novel therapeutic strategies for specific diseases.